2018
DOI: 10.1039/c8pp00176f
|View full text |Cite|
|
Sign up to set email alerts
|

Photobiomodulation: lasers vs. light emitting diodes?

Abstract: Photobiomodulation (PBM) is a treatment method based on research findings showing that irradiation with certain wavelengths of red or near-infrared light has been shown to produce a range of physiological effects in cells, tissues, animals and humans. Scientific research into PBM was initially started in the late 1960s by utilizing the newly invented (1960) lasers, and the therapy rapidly became known as "low-level laser therapy". It was mainly used for wound healing and reduction of pain and inflammation. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
110
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(115 citation statements)
references
References 120 publications
1
110
0
4
Order By: Relevance
“…[93][94][95] A recent review concluded that there were no substantial differences between lasers and LEDs for PBM applications provided all the other light parameters were equal. 96…”
Section: Laser Versus Noncoherent Lightmentioning
confidence: 99%
“…[93][94][95] A recent review concluded that there were no substantial differences between lasers and LEDs for PBM applications provided all the other light parameters were equal. 96…”
Section: Laser Versus Noncoherent Lightmentioning
confidence: 99%
“…This increase in acceptance is partly due to the increased availability of light-emitting diodes (LEDs) with wavelengths in the red and NIR regions and substantial levels of power density (up to 100 mW/cm 2 over fairly large areas). Most available evidence suggests that LEDs perform equally well compared to lasers of similar wavelengths and power density [4]. However, LEDs have the advantages of more safety, lower cost, and better suitability for home use.…”
Section: Introduction To Photobiomodulationmentioning
confidence: 99%
“…However, another non‐pharmacological strategy that has recently been shown to improve obesity‐induced dysfunctions is photobiomodulation therapy (PBMT). PBMT uses red or near‐infrared light, such as low‐level laser therapy (LLLT) or light‐emitting diodes (LEDs) therapy to induce biological effects.…”
Section: Introductionmentioning
confidence: 99%